The fixer [large type] - Finder, Joseph (Thorndike Press Large Print, 2015)
"When Rick Hoffman loses his job and apartment, his only option is to move back into--and renovate--the home of his miserable youth, now empty and in decay since his father's stroke. But when he starts to pull it apart, he makes an electrifying discovery that will put his life in peril--and change everything he thought he knew about his father"--Provided by publisher.